2017
DOI: 10.3389/fimmu.2017.00194
|View full text |Cite
|
Sign up to set email alerts
|

CD4 CTL, a Cytotoxic Subset of CD4+ T Cells, Their Differentiation and Function

Abstract: CD4+ T cells with cytotoxic activity (CD4 CTL) have been observed in various immune responses. These cells are characterized by their ability to secrete granzyme B and perforin and to kill the target cells in an MHC class II-restricted fashion. Although CD4 CTLs were once thought to be an in vitro artifact associated with long-term culturing, they have since been identified in vivo and shown to play important roles in antiviral and antitumor immunity, as well as in inflammation. Functional characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
343
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(360 citation statements)
references
References 70 publications
15
343
1
1
Order By: Relevance
“…This is particularly relevant to GB since glioma‐associated TAMs generally have suppressed MHCII expression (Qian et al, ; Schartner et al, ). Interestingly, glioma cells in HuR KO tumors showed higher MHCII expression (Figure S3) which can facilitate antigen presentation and make them targets of CD4+ cytotoxic effector cells (Accolla et al, ; Takeuchi & Saito, ; Thibodeau, Bourgeois‐Daigneault, & Lapointe, ). Regardless of the source, MHCII molecules within tumors are key to triggering anti‐tumor immune responses (Accolla et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant to GB since glioma‐associated TAMs generally have suppressed MHCII expression (Qian et al, ; Schartner et al, ). Interestingly, glioma cells in HuR KO tumors showed higher MHCII expression (Figure S3) which can facilitate antigen presentation and make them targets of CD4+ cytotoxic effector cells (Accolla et al, ; Takeuchi & Saito, ; Thibodeau, Bourgeois‐Daigneault, & Lapointe, ). Regardless of the source, MHCII molecules within tumors are key to triggering anti‐tumor immune responses (Accolla et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The graph below shows the mean densitometric values (±SEM) for the bands expressed as area under the curve (AUC). *p < .05; **p < .005; ***p < .0001 Takeuchi & Saito, 2017;Thibodeau, Bourgeois-Daigneault, & Lapointe, 2012). Regardless of the source, MHCII molecules within tumors are key to triggering anti-tumor immune responses (Accolla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of IFNγ to CHIKV‐induced inflammation remains unclear, however, recent studies have suggested that CD4 + T cells might mediate CHIKV arthritic disease through the secretion of proteins other than IFNγ. RNA‐Seq analysis of CHIKV‐infected mouse footpads at the peak of swelling revealed highly induction of Granzyme A, a serine protease produced by NK cells, CD8 + T cells, and Th1 CD4 + T cells . Furthermore, deficiency of Granzyme A (GzmA −/− ) or treatment with Serpinb6b—a Granzyme A inhibitor—in mice abolished CHIKV‐induced joint swelling without affecting viremia.…”
Section: Role Of Cell‐mediated Immunity In the Development Of Chikv‐imentioning
confidence: 99%
“…Recent studies have shown that Th cells with a similar Eomes-expressing phenotype are generated under chronic inflammatory conditions associated with chronic viral infection, such as cytomegalovirus and human immunodeficiency virus 1, or can be induced within tumor microenvironments by immunomodulation. [73][74][75] Therefore, the developmental processes of Eomes+ Th cells in the CNS under chronic inflammation will provide other therapeutic means for preventing transition of the disease from RR-MS to SP-MS ( Fig. 3).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%